2022
DOI: 10.7150/jca.66067
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LASTR promote lung cancer progression through the miR-137/TGFA/PI3K/AKT axis through integration analysis

Abstract: Background: Long noncoding RNAs (LncRNAs) are widely involved in the physiological and pathophysiological processes of cells. This study sought to identify novel lncRNAs that play key roles in progression of lung cancer. Methods: Cells were purchased from the Cell Bank of Type Culture Collection of the Chinese Academy of Sciences. Public lung cancer data were retrieved from The Cancer Genome Atlas database. Statistical analyses were performed using SPSS, R and GraphPad Prism 8 software. Results: Bioinformatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is known that breast cancer promote the activity of SART3 through the action of LINC02651 [ 43 ]. Furthermore, in stomach adenocarcinomas and lung cancer, LINC02657 is associated with tumor proliferation and metastasis [ 44 , 45 ]. LINC02154 accelerates the progression of hepatocellular carcinoma by activating PI3K-AKT [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that breast cancer promote the activity of SART3 through the action of LINC02651 [ 43 ]. Furthermore, in stomach adenocarcinomas and lung cancer, LINC02657 is associated with tumor proliferation and metastasis [ 44 , 45 ]. LINC02154 accelerates the progression of hepatocellular carcinoma by activating PI3K-AKT [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays an essential role in regulating plant metabolisms. However, research has demonstrated that LASTR modulates the activity of the U4/U6 recycling factor SART3 to boost cancer fitness [ 30 ], and also modulates the activity of the miR-137/TGFA/PI3K/AKT axis to accelerate lung cancer progression [ 31 ]. However, no study has reported a direct correlation between LASTR and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A new class of lncRNAs has gradually become a research hotspot in various cancer fields in recent years. Some studies have found that abnormal expression of lncRNAs is associated with the occurrence and progression of LUAD and some lncRNAs may be highly correlated with prognosis ( Spizzo et al, 2012 ; Cao et al, 2022 ; Xia et al, 2022 ). However, studies on m7G-related lncRNA predicting LUAD survival are scanty.…”
Section: Discussionmentioning
confidence: 99%